Cognitive impairment and the gut-brain axis during 2014–2023: a bibliometric analysis - He, Jindi; Wu, Jiaxun; Liu, Juan; Wu, Hangcai; Hua, Heliu (Frontiers in Neurology, 2024)
The burden on society grows as the number of individuals with cognitive impairment rises. Numerous research have discovered a connection between cognitive impairment and the gut-brain axis, which is useful in examining the pathophysiology of cognitive impairment and potential therapeutic approaches. As a result, this article explores developments and trends in the research concerning the gut-brain axis and cognitive impairment through a bibliometric analysis of the contributions made by various countries/regions, institutions, authors, and journals.We looked for articles on gut-brain axis and cognitive impairment from 2014 to 2023 in the Web of Science Core Collection. For the descriptive analysis, figures and tables were taken using GraphPad Prism 6 and WPS Office 2024. For the visual analysis of the countries/regions, institutions, authors, and keywords, VOSviewer was utilized.